Challenges and opportunities for biochar to promote circular economy and carbon neutrality - Kurniawan, Tonni Agustiono (2023)
Biochar, derived from unused biomass, is widely considered for its potential to deal with climate change problems. Global interest in biochar is attributed to its ability to sequester carbon in soil and to remediate aquatic environment from water pollution. As soil conditioner and/or adsorbent, biochar offers opportunity through a circular economy (CE) paradigm. While energy transition continues, progress toward low-emissions materials accelerates their advance towards net-zero emissions. However, none of existing works addresses CE-based biochar management to achieve carbon neutrality. To reflect its novelty, this work provides a critical overview of challenges and opportunities for biochar to promote CE and carbon neutrality. This article also offers seminal perspectives about strengthening biomass management through CE and resource recovery paradigms, while exploring how the unused biomass can promote net zero emissions in its applications. By consolidating scattered knowledge in the body of literature into one place, this work uncovers new research directions to close the loops by implementing the circularity of biomass resources in various fields. It is conclusive from a literature survey of 113 articles (2003-2023) that biomass conversion into biochar can promote net zero emissions and CE in the framework of the UN Sustainable Development Goals (SDGs). Depending on their physico-chemical properties, biochar can become a suitable feedstock for CE. Biochar application as soil enrichment offsets 12% of CO2 emissions by land use annually. Adding biochar to soil can improve its health and agricultural productivity, while minimizing about 1/8 of CO2 emissions. Biochar can also sequester CO2 in the long-term and prevent the release of carbon back into the atmosphere after its decomposition. This practice could sequester 2.5 gigatons (Gt) of CO2 annually. With the global biochar market reaching USD 368.85 million by 2028, this work facilitates biochar with its versatile characteristics to promote carbon neutrality and CE applications.